Investigation of seasonal prevalence of low pathogenic avian influenza (LPAI) in a heterogeneous wild waterfowl population in Pretoria - Phiri, Thandeka P. (Vaal University of Technology, 2018)
Influenza-A virus is a single stranded negative sense RNA virus that is a member of a Orthomyxoviridae group. The virus is diverse and consists of 16 haemagglutinin (H) and 9 neuraminidase (N) glycoproteins subtypes that form a serotype. Avian influenza virus (AIV) has been detected in more than 100 bird species from 26 different families, although Anseriformes and Charadriiformes are considered the natural hosts of the virus. A 12-month study was conducted at the African Pride Irene Country Club lodge in Pretoria where the prevalence of AIV was monitored in a community of wild birds. The African Pride Irene Country Club lodge houses a population of wild bird species such as Egyptian geese (Alopochen aegytptiaca), Yellow-billed duck (Anas undulata), Red knobbed coot (Fulica cristata), African sacred ibis (Threskiornis aethiopicus) and Hadeda ibis (Bostrycha hagedash). A total of 3674 faecal samples were collected over a period of 12 months and screened for AIV group using the Matrix gene (M-gene) real time reverse-transcriptase PCR (rRT-PCR). Positive samples were submitted for virus isolation in embryonated chicken eggs. In addition, the RNAs were screened using H5 and H7 subtype specific rRT-PCR and a conventional universal RCR assay that targets the HA gene was also used. Polymerase Chain Reaction (PCR) products were requenced using Sanger sequencing and the viral isolates were subjected to Next Generation sequencing (NGS). Twenty percent of the samples tested positive for the AIV group and four virus subtypes were identified. One virus isolate was identified through NGS as H3N6; two through conventional PCR and Sanger sequencing as H9Nx and H6Nx. Of the twenty percent samples that tested positive for AIV 98% were identified as H7Nx by subtype specific through rRT-PCR. The highest frequency of AIV positive samples was detected between the months of January and February 2017 (20%), with smaller peaks detected in february and March 2016 (0.3%). Lower peaks were also detected between the months July and November 2016 (0.1%), respectively. A high prevalence of AIV was detected in the late summer months with a frequency of 65% positive, although a low prevalence was also detected in the autumn (0.6%) winter (0.6%) and spring 0.08%). Thus, the study provides a valuable insight into the seasonal prevalence of AIV in a heterogeneous wild duck population in Gauteng Province.
M. Tech. (Department of Biotechnology, Faculty of Applied and Computer Science), Vaal University of Technology.
Keywords: Pathogenic avian influenza (LPAI); Wild waterfowl; RNA virus; Avian influenza virus (AIV); Dissertations, Academic -- South Africa.; Avian influenza A virus.